2021
DOI: 10.3389/fpsyg.2021.600712
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Change in the Relationships Between Leader-Member Exchange/Coworker Exchange and Newcomer Performance: A Latent Growth Modeling Approach

Abstract: This study examines whether and how the qualities of newcomers’ interpersonal relationships [i.e., leader-member exchange (LMX) and coworker exchange (CWX)] relate to their initial performance and how changes in the qualities of these relationships relate to the changes in performance. To test a latent growth model, we collected data from 230 newcomers at six time points over a 6-week period. The results showed that LMX quality is positively related to initial newcomer performance; however, changes in LMX qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 87 publications
0
6
0
Order By: Relevance
“…Higher scores indicate higher levels of CWX relationships. Previous studies have reported that the Chinese version CWX scale exhibits good validity and reliability (e.g., Cronbach’s α =.89 in Liu et al, 2021; Cronbach’s α = .86 in Tang et al, 2021; Cronbach’s α = .82 in Zhang et al, 2021). In the current sample, Cronbach’s α was measured as .90).…”
Section: Methodsmentioning
confidence: 97%
“…Higher scores indicate higher levels of CWX relationships. Previous studies have reported that the Chinese version CWX scale exhibits good validity and reliability (e.g., Cronbach’s α =.89 in Liu et al, 2021; Cronbach’s α = .86 in Tang et al, 2021; Cronbach’s α = .82 in Zhang et al, 2021). In the current sample, Cronbach’s α was measured as .90).…”
Section: Methodsmentioning
confidence: 97%
“…emotional support; Chiaburu and Harrison, 2008). In addition, Liu et al (2021) found that high CWX increases newcomers' job performance. Thus, we propose that CWX has a positive relationship with job performance.…”
Section: The Mediating Role Of Cwxmentioning
confidence: 96%
“…emotional support; Chiaburu and Harrison, 2008). In addition, Liu et al. (2021) found that high CWX increases newcomers' job performance.…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…In addition to machine learning, advanced analytic approaches, such as latent growth modeling or latent profile analysis, can be used to extract more nuanced findings. For instance, previous research has applied latent growth modeling to examine how the trajectory of changes in relational quality affect employee behavior in contexts such as the COVID-19 crisis (Matthews et al, 2022) and newcomer socialization (Liu, Lee, Li, & Li, 2021). Similarly, future research could use this approach to quantitatively examine the trajectory of RTC and related factors over time.…”
Section: Theory-testing Opportunitiesmentioning
confidence: 99%